From Epicentros to Fault Lines: Rewriting Central America from the Diaspora - Maritza Cárdenas (Studies in 20th & 21st Century Literature, 2013)
This essay examines how representations from the Central American diaspora rewrite the Central American imaginary. It focuses on the ways EpiCentroAmerica—a poetry collective who view themselves as Central American, but reject a single unifying vision of home by seeing themselves as part of a transregional and transnational community—challenge traditional configurations of Central America(n). This reinscription of the signifier Central America is best exemplified in the work of Salvadoran-American poet Marlon Morales, whose poem “Centroamérica is,” avoids suturing Central America with traditional nationalist geological images of volcanoes and the isthmus, in favor of constructing Central America as an amorphous abstract and material entity. This study argues that by eluding a stable definition of Central America, as well as by dislocating Central America from its dominant cartographic image of a landmass and questioning its ontological validity, Morales advances a thoroughly reconfigured understanding of Central America—one that accounts for its diaspora that is a part of Central America while being apart from the geopolitical borders of the isthmus. Thus through Morales’s piece, in conjunction with the artistic work of the EpiCentros, alternative visions of Central America that both contest and disrupt the North/South America divide are presented.
Keywords: Central America; diaspora; EpiCentroAmerica; transregional; transnational; geographical; isthmus